2019
DOI: 10.4103/njms.njms_53_17
|View full text |Cite
|
Sign up to set email alerts
|

Inferior alveolar nerve canal position in relation to mandibular molars: A cone-beam computed tomography study

Abstract: Objective:This study was carried out to prevent the risk of iatrogenic injuries to the inferior alveolar nerve (IAN) canal associated with various surgical interventions in the area of mandibular molars, by using cone-beam computed tomography (CBCT).Materials and Methods:The present retrospective study was carried out by using CBCT of 100 patients between 18 and 40 years of age group. The linear measurements were made in relation to the 1st and 2nd mandibular molars on both the sides. Linear distances between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The use of cone beam computed tomography (CBCT) in implantology, oral surgery, periodontology, orthodontics, and endodontics has greatly improved treatment success 1–7 . CBCT is the scan of choice for implant treatment planning as it offers greater measurement accuracy at lower radiation dosage, reduced scan time, and reduced artifacts compared to 2D and conventional medical CT imaging 8–13 .…”
mentioning
confidence: 99%
“…The use of cone beam computed tomography (CBCT) in implantology, oral surgery, periodontology, orthodontics, and endodontics has greatly improved treatment success 1–7 . CBCT is the scan of choice for implant treatment planning as it offers greater measurement accuracy at lower radiation dosage, reduced scan time, and reduced artifacts compared to 2D and conventional medical CT imaging 8–13 .…”
mentioning
confidence: 99%
“…Our values were difficult to compare with majority of papers, since some authors either grouped all patients of different age groups together and took the mean distances as Hsu et al [23], while other authors did not divide patient by age decades as we did in our study; Vidya et al [24] divided patients into three groups, GI from 25 to 30 years, GII 30-35 years, and GIII 32-42 years, no patients older than 42 years were included in the study. Kovisto et al [25] divided patient into three groups GI <18y, GII from 18 to 48 years and GIII more than 49 years.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies that used CBCT reconstructions employed different anatomical structures as the points of measurement, including bone margins, 15 the mental foramen, 16 or the root apices. 6 7 17 18 19 20 21 22 23 24 25 26 27 28 29 The relationship between the root apices and the bone margin or mental foramen is important for surgery, endodontic microsurgery, and implant procedures. Knowledge of the relationship between the root apices and the MC is important for endodontic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the relationship between the root apices and the MC is important for endodontic treatments. When the root apices were used as a reference point, some studies reported the position of the MC in millimetres, 6 7 17 18 19 20 21 23 24 26 27 28 29 while another described the contact or lack of contact between the MC and the root tips 25 and yet others described the position of the MC relative to the roots (i.e., lingual; buccal; interradicular; lingual and interradicular; apical/inferior/in-line with the apex/middle; lingual and inferior; buccal and inferior; or interradicular and inferior). 22 Studies that used root apices as the reference points and made measurements in millimetres used different definitions of the reference point on the MC.…”
Section: Discussionmentioning
confidence: 99%